2016
DOI: 10.2174/0929867323666160920110810
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin B in Depression

Abstract: Abstract:Vitamins are dietary components which are necessary for life. They play a major role in health and their deficiency may be linked to symptoms of psychiatric disorders. B vitamins are required for proper functioning of the methylation cycle, monoamine oxidase production, DNA synthesis and the repair and maintenance of phospholipids. Vitamin B deficiency could influence memory function, cognitive impairment and dementia. In particular, vitamins B1, B3, B6, B9 and B12 are essential for neuronal function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 96 publications
2
99
1
1
Order By: Relevance
“…The major discovery of the present study is that VitB6 produces several beneficial effects to prevent inflammation in lung. Traditionally, VitB6 may treat depression, stroke, anaemia, nausea during pregnancy, clogged arteries, eye diseases, diabetes and inflammation associated with rheumatoid arthritis . Recently, we have identified that VitB6 improves insulin resistance in Apoe −/− mice fed with high‐fat diet and prevents isocarbophos‐induced vascular dementia in rats .…”
Section: Discussionmentioning
confidence: 99%
“…The major discovery of the present study is that VitB6 produces several beneficial effects to prevent inflammation in lung. Traditionally, VitB6 may treat depression, stroke, anaemia, nausea during pregnancy, clogged arteries, eye diseases, diabetes and inflammation associated with rheumatoid arthritis . Recently, we have identified that VitB6 improves insulin resistance in Apoe −/− mice fed with high‐fat diet and prevents isocarbophos‐induced vascular dementia in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins are dietary components that are required for the proper function of the methylation cycle, monoamine oxidase production, DNA synthesis, and phospholipid repair and maintenance [15,16]. They play a major role in health, and their deficiencies may be linked to symptoms of neuronal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…They play a major role in health and their deficiency may be linked to symptoms of psychiatric disorders. [35] Studies on depression have shown that low folate and vitamin B12 serum levels seem to be associated with depression in the aged. [36,37] Systemic folate deficiency has been associated with macrocytic anemia and neuropsychiatric phenotypes.…”
Section: Discussionmentioning
confidence: 99%